Astrocytes in neural circuits controlling appetite and food intake. (February 2022) - Ellacott, Kate L.J.
Abstract: The regulation of feeding behaviour is a complex process controlled by neural circuits in the brain. In addition to neurons, genetic and pharmacological studies in animal models are revealing that glia, including astrocytes, are important components in these neural circuits. This review incorporates the latest evidence (published since 2019) from different brain regions for a contribution of astrocytes in regulating neural circuits controlling appetite and food intake, which encompasses eating when hungry to meet energetic need (homeostatic feeding) and hedonic eating for pleasure in the absence of energetic need (non-homeostatic feeding). The brain regions examined include the hypothalamus, dorsal vagal complex of the hindbrain, and the mesolimbic and cortico-striatal systems. The emerging theme of a potential astrocyte energetic model of neural circuit regulation in the context of feeding behaviour is evaluated. Graphical abstract: Image 1 Highlights: Astrocytes respond to changes in systemic energy balance. Experimental manipulation of astrocytes in animals impacts food intake. Astrocytes are directly responsive to hormones, showing changes in energetics. Improved understanding of regional astrocyte heterogeneity is needed. Could astrocyte metabolic reprogramming contribute to obesity?